China's political dynamics under XI Jinping - Bo, Zhiyue (World Scientific, 2017)
China watching is anything but being boring because Chinese politics is filled with dramas almost on a daily basis. In the past three years since Xi Jinping became general secretary of the Chinese Communist Party, the Chinese political drama has unfolded with a lot of twists and turns.